Modelling of SOLO’s car suspension system - Nurzaki Ikhsan; Ramlan Kasiran; M. Hanif Mat (Penerbit Universiti Kebangsaan Malaysia, 2024)
The use of a virtual analysis approach to develop and modify vehicle sub-system is becoming popular nowadays as it is less time consuming, reduces the workmanship and overall testing cost compared to the experimental approach. In this paper, an actual virtual suspension system based on UiTM’s Perodua Eco Challenge (PEC) competition full-body vehicle named SOLO was modelled using multi-body dynamic software, MSC/ADAMS Car. The virtual suspension system model was developed starting from identifying the components’ hard points, parameter setting, and joint type between the suspension components. The complete model was simulated using a static vertical parallel movement test with 30 mm as the selected bump travel movement. Following that, the values of kinematic and compliance of toe, camber and caster change were obtained. It was found that the front toe change was negative when subjected to wheel bound at 30mm (-0.3o), while the trend is opposite with the rear toe change (0.2o). Camber and caster change shows similar trends for both front and rear suspension system. Further analysis was then done to study the dynamic performance and suspension improvement after the virtual suspension system is verified.